DISSOCIATING REALITIES AND TRANS-FORMING SELF IN DAVID EBERSHOFF’S THE DANISH GIRL - Kamelia Talebian Sedehi; Tay Lai Kit (Indonesian EFL Journal, 2017)
Since its film debut in 2015, The Danish Girl has garnered major attention on the novel which was originally published in 2000 by David Ebershoff. As portrayed evidently in both mediums, Einar Wegener is depicted as a transgendered individual who suffers from gender identity disorder. However, this paper intends to argue that Einar could potentially suffer from Dissociative Identity Disorder (DID), or more commonly referred to as multiple personality disorder. To specify, the current paper contends that Einar dissociates himself from the reality he is grounded in and becomes another character upon any overwhelming situation. Dissociation happens when the subject is subjected to extreme reality and breaks under pressure, thus, creating another persona as an act of self-protection to defend himself from the situation. As such, this article will shed light on the issue by providing textual evidences which helps in reading Einar as a patient of DID instead of being a transgender. Keywords: dissociation, dissociative identity disorder, multiple personality disorder, the danish girl, alter